Initial Audit Investigating Physical Health Screening and Management of Neuropsychiatric Manifestations in Parkinson’s Disease (PD), Parkinson’s Disease Dementia (PDD) and Dementia With Lewy Bodies (DLB) on the Mental Health Services for Older Persons (MHSOP) Wards - Mohammed Qureshi; Taofeeq Elias; Olaomopo Ikuforiji; Chidinma Okafor; Samuel Cohen (BJPsych Open, 2025)
Aims: To improve the overall quality of healthcare for mental health inpatients with a diagnosis of PD, PDD or DLB (with neuropsychiatric manifestations such as depression, agitation, psychosis or cognitive deficits), by improving: (a) physical healthcare screening and (b) the collaborative approach between inpatient mental health teams and PD specialists.